Waliyyullah dalam Tafsir Sufistik: Kajian Pemikiran Ibnu ‘Arabi terhadap QS. Yunus 62–64 - Amanatus Solekhah; Ikhwanudin; Muhammad Nur Amin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the concept of waliyyullâh (friends of Allah) in the Qur'an according to Ibn 'Arabi's interpretation. The background of this research is the public misunderstanding in perceiving the figure of a wali, which is often mystical and exaggerated, potentially leading to polytheistic practices. This study aims to analyze Ibn 'Arabi's definition, characteristics, and interpretive method regarding waliyyullâh based on QS. Yunus verses 62-64. This research employs a qualitative method with a library research type and a thematic (maudhu'i) interpretive approach. Primary data sources include Ibn 'Arabi's Tafsīr al-Qur'ān al-Karīm, as well as Futūḥāt al-Makkiyyah and Fuṣūṣ al-Ḥikam as supporting sources. The findings reveal that according to Ibn 'Arabi, waliyyullâh are servants who achieve perfect proximity to Allah through the station of fanā' (annihilation of the ego) and become manifestations (tajalli) of divine attributes within the framework of Wahdat al-Wujūd (Unity of Existence). The characteristics of waliyyullâh include: having no fear or sorrow, possessing perfect faith (al-yaqīn) and piety (taqwā) encompassing heart purification, and receiving glad tidings (al-busyrā) in the form of inner tranquility in this world and spiritual experience (dhawq) in the hereafter. Ibn 'Arabi's interpretive method is characterized as ishārī (Sufi) with a ta'wīl method based on kashf (spiritual unveiling). This research contributes to correcting public misperceptions about awliyā and preventing polytheistic practices. Further research is recommended to conduct comparative studies with other Sufi exegetes and field research on social reception of the waliyyullâh concept among Muslim communities.